Legends And Customs Of Svaneti - Nikoladze-Lomsianidze, Nora (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
Legend is the independent genre of folklore, which is based on the religious faith and represents the fantastic stories as reality. The notes about legends are few in scientific literature, the reason is that legend is considered as the variation of the fairy tale which is a mistake. The famous researcher Mikheil Chikovani gave the legend its proper place among the different genres of fairy tale. The legend originates from the ancient times. We know that the people of Mesopotamia had legends in the III century B.C. Originally, legend stood for the life of saints and the passages reflecting their martyrdom, they were read during church services dedicated to those saints. After that the term denotes Christian (non-Christian as well) religious-didactic stories. Besides the church people, the legends were also assigned to secular people - kings, lords, famous public men and their lives were veiled in religious framework. Researchers envisage the reflection of reality if legends. The same is confirmed by Ilia Tchavtchavadze, Akaki Tsereteli, Vaja-Pshavela. Konstantine Gamsakhurdia recognizes the legend as a condenser of history. According to him “the history of every nation originates from legends”. The same idea is expressed by Giuseppe Cociarro in his book “the history of European folk culture”. As it is well-known Christian religion was being formed in the clash with pagan faith in Georgia. Holy scriptures and Apocryphal literature prepared the nourishing sole for creating and spreading numerous new legends. Legends are prevalent in different parts of Georgia. In this case the subject matter of our interest is the Svanetian legens and customs. This part of Georgia keeps the legends of different origin - cosmogon, apocryphal, biblical flood (great and small floods) time, historical, etc. reflecting the Christian as well as pagan faith. There are also legends which convey the both traits. Svaneti is also rich with its customs. The work presents the relevant examples.